2006
DOI: 10.1021/cg050508j
|View full text |Cite
|
Sign up to set email alerts
|

Process Development Strategy to Ascertain Reproducible API Polymorph Manufacture

Abstract: The present example illustrates the application of a consistent process development strategy to ascertain reproducible active pharmaceutical ingredient (API) polymorph manufacture. Key methodologies are illustrated using a Novartis API and carbamazepine as model substances. In the present example, the Novartis API was synthesized in the final chemical step by hydrolysis followed by acidification. The process was investigated in four steps: First, solid-liquid equilibrium studies were carried out in several sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…Different crystal modifications are likely to produce crystals of varying shapes [6,17] and solid materials with varying physical properties (melting point, density, hardness, solubility) [18][19][20]. Consequently, polymorphism directly affects downstream operations, handling of the bulk particles and the bioavailability of the drug substance [21,22]. This is also true for solvates, salts and amorphous solids [8].…”
Section: Introductionmentioning
confidence: 99%
“…Different crystal modifications are likely to produce crystals of varying shapes [6,17] and solid materials with varying physical properties (melting point, density, hardness, solubility) [18][19][20]. Consequently, polymorphism directly affects downstream operations, handling of the bulk particles and the bioavailability of the drug substance [21,22]. This is also true for solvates, salts and amorphous solids [8].…”
Section: Introductionmentioning
confidence: 99%
“…4 Hence, characterization of all possible polymorphs and identifying the desired form to design a reliable process for its consistent production is critical for a successful drug development. [5][6][7] But, even after a thorough search, new polymorphs can suddenly appear or previously known polymorphs can disappear at any stage of the process development. [8][9][10][11] This inability to control the appearance of polymorphs clearly demonstrates the lack of understanding in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The development strategy used by Novartis to obtain reproducible polymorphic composition of drug substances was illustrated using carbamazepine as the example, and it was shown how physicochemical characterization methods were used to develop a simple robust process that could supply approximately 1000 kg of a stable polymorph for clinical trials and market introduction. 33 Other methods of initiating nucleation in crystallization processes have been studied with the aim of obtaining better control over the isolated product. A study has been reported where the effect of ultrasound irradiation on the polymorphic composition, particle size distribution, and heat transfer characteristics in the batch cooling crystallization of glycine was evaluated.…”
Section: Studies Of Preparative and Isolation Methodsmentioning
confidence: 99%